The change of psychosocial stress factors in families with infants and toddlers during the COVID-19 pandemic. A longitudinal perspective on the CoronabaBY study from Germany - Buechel, Catherine; Friedmann, Anna; Eber, Stefan; Behrends, Uta; Mall, Volker; Nehring, Ina (Frontiers in Pediatrics, 2024)
Background: Over nearly three years, the COVID-19 pandemic has had a lasting impact on people's lives and mental health worldwide with its far-reaching restrictions and concerns about infections and other personal consequences. Families were particularly affected and showed increased stress and psychological problems. Long-term effects cannot be ruled out. So far, data on young families are sparse. The present longitudinal analysis (n = 932) of the CoronabaBY study investigated the development of parenting stress, parental affective symptoms, and child's mental health in young families with children aged 0-3 years in Germany as well as potential influencing factors. Methods: The observational study includes two measurement points over the course of the pandemic (baseline and follow-up). Data was collected by app using standardized questionnaires.Results: N = 932 participants, mainly mothers (94.7%) born in Germany (93.1%) with higher education (61.3% with at least high school diploma) and a comfortable financial situation participated in the longitudinal study. Children were on average 14.7 months old at baseline (SD: 12, range: 1-39 months). While the proportion of parents who perceived the pandemic as stressful decreased significantly from baseline (60%) to follow-up (52.3%), the proportion with parenting stress increased significantly (from 40.1% to 45.4%). Both parental and child mental health problems remained constant over time, with infants crying/feeding/sleeping problems ranging above pre-pandemic comparative data. Most predictive for high parenting stress at follow-up was high parenting stress at baseline. This was also true for parental affective symptoms (depression/anxiety) and child mental health problems. Conclusions: Despite faded pandemic restrictions, parents remained burdened. Support services do not appear to have been sufficient to help families out of their stressful situation. Our results indicate a need for action regarding low-threshold services that effectively reach affected families.